ANALISIS RITEM LAGU-LAGU ALU KATENTONG NAGARI PADANG LAWEH KABUPATEN TANAH DATAR - Wahyu Prima Nelga; Wimbrayardi Wimbrayardi; Marzam Marzam (SENDRATASIK UNP, 2018)
Abstract This study aimed to analyze the alu katentong rhythm in Nagari Padang Laweh, Tanah Datar Regency. This analysis was conducted in order to clarify the rhythm of Alu Katentong art songs. Alu katentong has various rhythms. From the various rhythms, analysis was done to see some rhythms that had the same pattern with each other. The results of the study showed that there were some similarities between the rhythm of one alu and other alu that contained in the same or different songs. This study proved that, there were 7 different types of rhythms in different songs and with different names. Beside the rhythm, the various beep tone from 3 different types of wood also became the identity of alu katentong. Keywords: Analysis and Rhythm.